Effect of ACE mutations on blood ACE phenotype parameters. - Olga V Kryukova; Dmitry O Korostin; Vera A Belova; Valery V Cheranev; Zhanna A Repinskaia; Igor V Uporov; Steven M Dudek; Olga A Kost; Denis V Rebrikov; Sergei M Danilov (PLoS ONE, 2024)
Background Analysis of existing mutations of Angiotensin-I-Converting Enzyme (ACE) led us to hypothesize that the carriers of damaging ACE mutations (accompanied by low ACE levels) could be at risk for the development of late-onset Alzheimer's disease (AD). Methodology/principal findings We quantified blood ACE levels in EDTA-containing plasma from 15 patients with 11 different heterozygous ACE mutations and estimated the effects of these mutations on ACE phenotypes, using a set of mAbs to ACE and two ACE substrates. We confirmed prior observations that the relatively frequent Y215C mutation in the N domain of ACE (present in ~1% of the population) is associated with both Alzheimer's disease (AD) and reduced plasma levels of ACE (~50% of controls), indicating that it likely results in a transport-deficient protein. In addition, we identified another 4 mutations in both ACE domains (M118T, C734Y, V992M and V997M) which are also associated with decreased ACE levels in the blood, and, thus, could be putative risk factors for late-onset AD. One of these mutations, C734Y, is likely transport-deficient, while the other mutations appear to influence ACE catalytic properties. The precipitation of mutant M118T by mAb 2D1 and ACE mutant C734Y by mAb 3F10 increased 2-3-fold compared to native ACE, and therefore, these mAbs could be markers of these mutations. Also, we identified a mutation I989T, which is associated with increased ACE levels in the blood. Conclusions/significance Conducting a systematic analysis of blood ACE levels in patients with ACE mutations holds promise for identifying individuals with low blood ACE levels. Such individuals may be at increased risk for late-onset AD. The patients with transport-deficient ACE mutations may benefit from therapeutic treatment with a combination of chemical and pharmacological chaperones and proteasome inhibitors, as was demonstrated previously using a cell model of the transport-deficient ACE mutation, Q1069R [Danilov et al, PLoS One, 2010].